Towards single‐atom photocatalysts for future carbon‐neutral application. Issue 3 (11th March 2022) - Zhang, Dongpeng; Li, Yanxiao; Li, Yi; Zhan, Sihui
Abstract: The implementation of carbon neutrality to achieve the goal of controlling global warming in the Paris Climate Agreement is currently the most important international climate issue. Efficient utilization of solar energy through photocatalysts is of great significance to the adjustment of energy structure. Single‐atom photocatalysts have excellent catalytic activity and selectivity in a variety of applications, including sustainable energy conversion, chemical synthesis, CO2 reduction, environmental remediation, and other areas, owing to their unique electronic structure and high atom usage. Here, we elaborated on the content and implementation direction of the carbon neutrality policy and demonstrated the design principles of single‐atom photocatalysts. Recent single‐atom synthesis strategies are summarized, and representative characterization methods have been shown to further reveal the structure–performance relationship. Then, we focus on the application of single‐atom photocatalysts in CO2 reduction, sustainable energy conversion, and environmental remediation. Finally, the opportunities and challenges in the application of single‐atom photocatalysts were discussed based on its current development. Abstract : The implementation of carbon neutrality to achieve the goal of controlling global warming in the Paris Climate Agreement is currently the most important international climate issue. The efficient utilization of solar energy through single‐atom photocatalysts has broad application prospects in the fields of sustainable energy conversion, chemical synthesis, CO2 emission reduction, and environmental remediation.